Борис Годунов - Скрынников Руслан Григорьевич (Серия "Страницы истории нашей Родины", 1983)
Экземпляры: абонемент (20020101) / Инвентарный номер: 6809 / Цена: 0.65 / Авт.знак: С 45 / ГРНТИ: 03 / ББК: 63. 3 (2) 4